Researcher sherlockiana pedagogical perspective - Pineda, Diego Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The text present the conceptual development about an author denominated pedagogical research. It explains from the reading and interpretation of Sir Arthur Konan Doyle texts and its main character Sherlock Holmes, some clues on order to do the pedagogical researcher: personal passion for the knowledge, curiosity and astonished, diligence and discipline, logical and imaginatively ability. At same time it explains the possibility of free and public discussion in the university and the strength in the writing and the community academic formation as characteristic of pedagogical researcher. The text is development in three parts: first makes references to the characteristics of researcher, second it is about the process of research and performance characteristics of itself and last it explains the institutional conditions which permit its action and implication into society.